Increased Interest And Understanding of Generation Z In Investing Through Capital Market Schools 2024 - Setiawan, Naldi; Wijaya, Ermy (Universitas Dehasen Bengkulu, 2024)
The capital market is a market for various long-term financial instruments with a term of more than one year, such as shares, bonds, mutual funds, and various derivative instruments from securities or securities. Talking about the capital market, of course, cannot be separated from investment. The investment process includes understanding the basics of investment decisions and how to organize activities in the investment decision process. To understand the investment process, an investor must first know several basic investment concepts, which will become the basis for each stage of making investment decisions. This investment is like a seed planted by an investor in a company or agency which will later grow. The capital market is also known as the stock exchange. The Indonesian Stock Exchange Investment Gallery (GI-BEI) is a means to introduce the capital market from an early age to the academic world. Through the Generation Z capital market education program, it is hoped that it will become a driving force in supporting socialization and education programs in the investment sector and can also attract more new issuers and increase the number of investors in the capital market from generation z and the community.